Clinical review: The suggested management pathway for urticaria in primary care. Issue 10 (5th October 2022) - Ryan, Dermot; Tanno, Luciana K.; Angier, Elizabeth; Clark, Evangéline; Price, David; Zuberbier, Torsten; Maurer, Marcus
Abstract: Background: Urticaria is a common condition presenting both as acute and chronic disease within primary care. To those without specialist training it is poorly understood from the points of view of diagnosis and management. It causes a considerable disease burden to sufferers with marked impact on quality of life. Purpose of this review: The recent publication of the EAACI/GA²LEN/EuroGuiDerm/APAAACI Guideline for the Definition, Classification, Diagnosis and Management of Urticaria guideline prompted us to take this excellent resource and re‐configure its findings and recommendations to a non‐specialist audience with particular reference to the needs of the primary care team.